ICRH antenna S-matrix measurements and plasma coupling characterisation at JET. (22nd February 2018) - Monakhov, I.; Jacquet, P.; Blackman, T.; Bobkov, V.; Dumortier, P.; Helou, W.; Lerche, E.; Kirov, K.; Milanesio, D.; Maggiora, R.; Noble, C.
Abstract: The paper is dedicated to the characterisation of multi-strap ICRH antenna coupling to plasma. Relevance of traditional concept of coupling resistance to antennas with mutually coupled straps is revised and the importance of antenna port excitation consistency for application of the concept is highlighted. A method of antenna S -matrix measurement in presence of plasma is discussed allowing deeper insight into the problem of antenna-plasma coupling. The method is based entirely on the RF plant hardware and control facilities available at JET and it involves application of variable phasing between the antenna straps during the RF plant operations at >100 kW. Unlike traditional techniques relying on low-power ( 10 mW) network analysers, the applied antenna voltage amplitudes are relevant to practical conditions of ICRH operations; crucially, they are high enough to minimise possible effects of antenna loading non-linearity due to the RF sheath effects and other phenomena which could affect low-power measurements. The method has been successfully applied at JET to conventional 4-port ICRH antennas energised at frequencies of 33 MHz, 42 MHz and 51 MHz during L-mode plasma discharges while different gas injection modules (GIMs) were used to maintain comparable plasma densities during the pulses. The S -matrix assessment and its subsequent processing yielding 'global' antenna coupling resistances in conditions of equalised port maximum voltages allowed consistent description of antenna coupling to plasma at different strap phasing, operational frequencies and applied GIMs. Comprehensive experimental characterisation of mutually coupled antenna straps in presence of plasma also provided a unique opportunity for in-depth verification of TOPICA computer simulations.